GIS-based mapping of water-level fluctuations (WLF) and its impact on groundwater in an Agrarian District in Tamil Nadu, India - P. J. Sajil Kumar (Environment, Development and Sustainability, 2021)
This study describes the results of groundwater table variation in Thanjavur District before and after the monsoon seasons. Groundwater-level data acquired by the field measurement and the elevation data have been obtained from the topographic survey. Groundwater is the major source for different sectors in this region, and the major portion was used for irrigation. The impacts of geology, soil types, topographic elevation, land-use changes were critically analyzed and identified that these factors are controlling the infiltration capacity. The maximum fluctuation in the water table was 2~m below the ground level; still, 50% of the study area is under threat of overexploitation. This is projecting to a severe shortage in water supply soon. Groundwater quality is threatening by the saline intrusion in the coastal region, and the irrigation return flows inland. The spatial variation maps were useful in visualizing the seasonal water level and fluctuation in Thanjavur. A proper monitoring system, efficient irrigation practices, and effective groundwater recharge structures are recommended.
Keywords: 330; Groundwater; Water-level fluctuation; GIS; Thanjavur